Dosimetric and radiobiological evaluation of four radiation techniques in preoperative rectal cancer radiotherapy. Issue 4 (20th December 2021) - Softa, Vasiliki; Kiouvrekis, Yiannis; Makridou, Anna; Kappas, Constantin; Kyrgias, George; Theodorou, Kiki
Abstract: Purpose: To compare tumour dose distribution, conformality, homogeneity, normal tissue avoidance, tumour control probability (TCP) and normal tissue complication probability (NTCP) using 3D conformal radiation therapy (3DCRT), 3- and 4-field intensity-modulated radiation therapy (IMRT) and volumetric-modulated arc therapy (VMAT) in patients with locally advanced rectal cancer. Materials and methods: Twenty-four patients staged T 1–3 N + M 0 with locally advanced rectal cancer underwent neoadjuvant chemoradiation therapy. Four different radiotherapy plans were prepared for each patient: 3DCRT, 3- and 4-field IMRT and VMAT are evaluated for target distribution using CI and homogeneity index (HI), normal tissue avoidance using D max, V 45, V 40, V 50 and TCP and NTCP using the Lyman–Kutcher–Burman model. Results: VMAT has better HI (HI = 1·32) and 3DCRT exhibited better conformality (CI = 1·05) than the other radiotherapy techniques. With regard to normal tissue avoidance, all radiotherapy plans met the constraints. D max in the 3DCRT plans was statistically significant ( p = 0·04) for bladder and no significant differences in V 40 and V 50 . In the bowel bag, no significant differences in D max for any radiotherapy plan and V 40 was lower in 3DCRT than VMAT ( p = 0·024). In the case of femoral heads, 3DCRT has a statistically significant lower dose on D max than 4-field IMRT ( p = 0·00 « 0·05). VMAT has the biggest TCP (80·76%) than the other three radiotherapy plans. With regard to normal tissue complications, probabilities were shown to be very low, of the order of 10 -14 and 10 -41 for bowel bag and femoral heads respectively. Conclusions: It can be concluded that 3DCRT plan improves conformity and decreases radiation sparing in the organ at risks, but the VMAT plan exhibits better homogeneity and greater TCP.